“A little war that shook the court”: comment on the judgement of the European Court of Human Rights in the case of Georgia v. Russia (ii) of 21 January 2021 - Marcinko, Marcin (Polish Review of International and European Law, 2022)
The long-awaited judgement of the European Court of Human Rights in the case of Georgia v. Russia (II) of 21 January 2021 evokes rather ambivalent assessment. On the one hand, the Court found that the Russian authorities were responsible for systematic violations of human rights related to Russia’s participation in the “five-day war”, and on the other hand, the Court limited this responsibility only to the “occupation phase”, i.e. the period after the ceasefire on 12 August 2008. As for the “active phase of hostilities”, i.e. the period of armed clashes from 8 to 12 August 2008, the Court found that due to the lack of “effective control” by Russia, the Court could not apply any model of jurisdiction to any of the alleged violations of the Right to Life under the ECHR. This comment is an analysis of the reasoning of the Court in relation to the most important issues in this case: extraterritorial jurisdiction in the context of international armed conflict (including the issues of effective control over an area and State agent authority and control over individuals), the relationship between the ECHR and international humanitarian law and the investigative obligation under Article 2 of the ECHR.